2013
DOI: 10.1002/lary.24196
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term results of endoscopic sinus surgery–oriented treatment for chronic rhinosinusitis with asthma

Abstract: FESS-oriented multimodality treatment improves CRS with asthma significantly and persistently. Asthma control level improved. Antiasthma medication use and pulmonary function remained stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 23 publications
3
23
0
1
Order By: Relevance
“…Chen et al previously examined ACT outcomes after ESS. They demonstrated improvement in ACT categorization of asthma control, but failed to show improvement in mean postoperative ACT scores.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al previously examined ACT outcomes after ESS. They demonstrated improvement in ACT categorization of asthma control, but failed to show improvement in mean postoperative ACT scores.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown improvements in asthma control following either surgery or medical CRS treatment . Among 17 steroid‐dependent patients with difficult asthma, surgery for CRS and nasal polyposis reduced airflow obstruction, and nine patients could be weaned off oral corticosteroids completely .…”
Section: Does Treatment Of Comorbidities Improve Difficult Asthma?mentioning
confidence: 99%
“…Most published studies are of a retrospective nature, [1,8,21,22] or do not include a non-surgical control group [2,3,7,9,17,18].…”
Section: Limitationsmentioning
confidence: 99%
“…Both issues pose significant problems for the validity of the research: retrospective studies, by nature, are at risk of various sorts of bias. Many articles (although not all) report symptomatic relief of asthma following sinonasal surgery [1][2][3][4][7][8][9]. However, without a control group with similar baseline characteristics to compare them with, it is impossible to determine whether this subjective relief might be due to the placebo effect or just an expression of improved quality of life (QoL) due to improved nasal symptoms.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation